The Development of Scientific Theories of Metaphor Translation from the Cultural Point of View - kizi, Makhmudova Gulbakhor Bakhrom (Researchparks Publishing, 2023)
This article concerns about the essential theories of metaphor translation, their specific features, differences and similarities and the development of metaphor theory throughout the years. In addition, here is highlighted the well-known scholars, their scientific works are also given and discussed, the linguists attitude to the issue is explained.